Piriformospora indica and Azotobacter chroococcum Consortium Facilitates Higher Acquisition of N, P with Improved Carbon Allocation and Enhanced Plant Growth in Oryza sativa - Prasun Bandyopadhyay; Bal Govind Yadav; Srinivasan Ganesh Kumar; Rahul Kumar; Karl-Heinz Kogel; Shashi Kumar (Journal of Fungi, 2022)
The soil microbiome contributes to nutrient acquisition and plant adaptation to numerous biotic and abiotic stresses. Numerous studies have been conducted over the past decade showing that plants take up nutrients better when associated with fungi and additional beneficial bacteria that promote plant growth, but the mechanisms by which the plant host benefits from this tripartite association are not yet fully understood. In this article, we report on a synergistic interaction between rice (Oryza sativa), Piriformospora indica (an endophytic fungus colonizing the rice roots), and Azotobacter chroococcum strain W5, a free-living nitrogen-fixing bacterium. On the basis of mRNA expression analysis and enzymatic activity, we found that co-inoculation of plant roots with the fungus and the rhizobacterium leads to enhanced plant growth and improved nutrient uptake compared to inoculation with either of the two microbes individually. Proteome analysis of O. sativa further revealed that proteins involved in nitrogen and phosphorus metabolism are upregulated and improve nitrogen and phosphate uptake. Our results also show that A. chroococcum supports colonization of rice roots by P. indica, and consequentially, the plants are more resistant to biotic stress upon co-colonization. Our research provides detailed insights into the mechanisms by which microbial partners synergistically promote each other in the interaction while being associated with the host plant.